Measuring the Amount of Melatonin in Twelve Medicinal and Edible Plants - ALQaragholy, Hanan H.; Ayyad W. ALShahwany (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Melatonin (Mel) is a conserved chemical that has been found in far-removed evolutionary organisms. Additionally, it has been proposed that Mel is a stand-alone plant growth regulator whose action is presumably similar to that of IAA and may moderate the effects of other plant growth regulators. Twelve medicinal herbs were divided into parts, and their melatonin concentrations were measured. These plants Ziziphus spina-christi, , Eucalyptus comaldulensis, Melissa officinalis,  Alhagi maurorum, Lavandula angustifolia, Vitex agnus-sactus, Piper nigrum, Hordeum vulgare, Matricaria chamomilla, Borago  officinalis, Solanum lycopersicum and Citrus aurantium  . Methanol was used to extract melatonin from dried plant parts at room temperature for 6 hours. Then, cyclo (18) carbon was used to refine melatonin. Then, melatonin was analyzed with an reversed-phase chromatography )RP-C18(-approved high-performance liquid chromatography system "HPLC "technique with fluorescence detection and Thin layer chromatography "TLC". Melatonin contents in extracts of  Z.spina-christi, E. comaldulensis, M. officinalis, A. maurorum, L. angustifolia,V. agnus-sactus, P. nigrum, H. vulgare, M. chamomilla, B. officinalis, S. lycopersicum and C. aurantium  were 420.494, 418.831, 409.750, 408.248, 385.145,239.967, 232.299, 220.569,215.804, 201.862, 108.517 and  106.744  ng/g of plant dry weight, respectively. The extract of Z. spina-christi contained the most melatonin (420.494 ng/g of plant dry weight). Not only do Mel concentrations vary between species, but also within variants of the same species. Different environmental influences on plant growth and development during successive stages of seed morphological and physiological development may cause variations in MEL contents.